IMPLEMENTATION OF TRAFFIC VIOLATION DETECTION AND TRAFFIC CONTROL - R. Karthikeyan (International Journal of Modern Agriculture, 2020)
The researchers show much interest in the identifying the control system for street lights using electrical energy. The conceptual idea involved in this project is monitoring the street light faults and control of the street lights in the control room and identify the person who is not obeying the traffic rule. The ultimate goal of the system is to warn the drivers through loudspeakers for their violation of rules they do during driving and sufficient time is provided to them to respond towards the incoming traffic position. Anyhow, whenever they violate the traffic rules the off-line checking is carried out by saving the datas of vehicle such as vehicle speed, GPS location, and other driving parameters are considered.